The Effect Of Esg Disclosure On Firm Value (Study Of Industrial Sector Companies Listed On The Indonesia Stock Exchange In 2021-2024) - Sherin Connelly Pasaribu; Fera Damayanti; Ira Grania Mustika (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) disclosure on firm value in industrial sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2024 period. ESG is an important indicator in assessing a company's sustainability commitment, while company value reflects investors' perceptions of the company's performance and prospects. This type of research is quantitative, using secondary data obtained from the company's Annual Report and Sustainability Report. The sample was selected using purposive sampling method, with a total of 33 observation data that had been filtered from outliers. The analysis technique used is multiple linear regression processed using IBM SPSS Statistics version 27. The results showed that partially, Environmental disclosure has a positive and significant effect on firm value, Social disclosure has no significant effect on firm value, and Governance disclosure has a negative and significant effect on firm value. Simultaneously, the three ESG disclosure variables have a significant effect on firm value. This study supports the importance of integrated ESG disclosure in shaping investor perceptions and driving long-term firm value.